The problem of values personality: structure and features of operation - Harkavets, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
In article discusses the features of the system of values of the individual. The analysis of the approaches to the definition of "system" and the qualitative differences, as well as the quality of the basic value system of the individual. Determined that the use of a planetary-autonomous model for examining the structure of the value system is the most appropriate person, as this model is much given to the principle of system approach.